SARS-CoV-2 seroprevalence among healthcare workers in a highly vaccinated Japanese medical center from 2020–2023 - Yan Yan; Kanami Ito; Hiroshi Fukuda; Shuko Nojiri; Wataru Urasaki; Takamasa Yamamoto; Yuki Horiuchi; Satoshi Hori; Kazuhisa Takahashi; Toshio Naito; Yoko Tabe (Human Vaccines & Immunotherapeutics)
Infection-induced SARS-CoV-2 seroprevalence has been studied worldwide. At Juntendo University Hospital (JUH) in Tokyo, Japan, we have consistently conducted serological studies using the blood residue of healthcare workers (HCWs) at annual health examinations since 2020. In this 2023 study (n = 3,594), N-specific seroprevalence (infection-induced) was examined while univariate and multivariate logistic regression analyses were performed to compute ORs of seroprevalence with respect to basic characteristics of participants. We found that the N-specific seroprevalence in 2023 was 54.1%—a jump from 17.7% in 2022, and 1.6% in 2021—with 37.9% as non-PCR-confirmed asymptomatic infection cases. Those younger than 50 (adjusted OR = 1.62; p < .001) and recipients with 4 doses or less of vaccine had a higher risk to be N-positive, ranging from 1.45 times higher for the participants with 4 doses (p < .001) to 4.31 times higher for the participants with 1 dose (p < .001), compared to those with 5 or more doses. Our findings indicate that robust vaccination programs may have helped alleviate symptoms but consequently caused asymptomatic spread in this hospital, especially among younger HCWs. Although having four doses or less was found to be associated with higher risk of infection, the optimal constitution and intervals for effective booster vaccines warrant further investigations.